The renaissance, the reformation, and the rise of nations - Fix, Andrew C.; Teaching Company ([Chantilly, VA ] : The Teaching Company, 2005)
Presents lectures delivered by Professor Andrew C. Fix tracing the course of European history from the middle of the fourteenth century to the early eighteenth century
pt. 4. lecture 37. The rise of absolutism in France ; lecture 38. Louis XIV ; lecture 39. Absolutism in Germany ; lecture 40. The Spanish monarchy ; lecture 41. The Dutch republic ; lecture 42. Constitutional monarchy in England ; lecture 43. The English Civil War ; lecture 44. Cromwell and the glorious revolution ; lecture 45. The scientific revolution-- the old science ; lecture 46. Preparing for change ; lecture 47. The revolution under way ; lecture 48. The early enlightenment 1680-1715
Lecturer: Andrew C. Fix
Keywords: Civilization, Medieval; Europe -- Civilization -- 14th century; Europe -- Civilization -- 15th century; Renaissance; Reformation; Middle Ages